A prospective 20‐year longitudinal follow‐up of dementia in persons with Down syndrome. Issue 9 (29th June 2017) - McCarron, M.; McCallion, P.; Reilly, E.; Dunne, P.; Carroll, R.; Mulryan, N.
Abstract: Goal: To examine dementia characteristics, age at onset and associated co‐morbidities in persons with Down syndrome. Method: A total of 77 people with Down syndrome aged 35 years and older were followed up from 1996 to 2015. The diagnosis of dementia was established using the modified ICD 10 Criteria and a combination of objective and informant‐based tests. Cognitive tests included the Test for Severe Impairment and the Down Syndrome Mental Status Examination; adaptive behaviour was measured using the Daily Living Skills Questionnaire, and data from the Dementia Questionnaire for People with Intellectual Disabilities have been available since 2005. Results: Over the 20‐year period, 97.4% ( 75 of 77 ) persons developed dementia with a mean age of dementia diagnosis of 55 years (SD = 7.1, median = 56 years). Clinical dementia was associated with cognitive and function decline and seizure activity. Risk for dementia increased from 23% in those aged 50 years to 80% in those aged 65 years and above. There were no differences by level of ID. Conclusion: The previously reported high risk levels for dementia among people with Down syndrome were confirmed in this data as was the relationship with late onset epilepsy. The value of the instruments utilised in tracking decline and helping to confirm diagnosis is further highlighted.